Surgical Outcomes and Recurrence in Adult Abdominal Cocoon (Sclerosing Encapsulating Peritonitis): A Systematic Review and Meta-Analysis of Pooled Proportions - Eko Nur Febrianto; Zuldi Erdiansyah; Reno Rudiman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Abdominal cocoon, also termed sclerosing encapsulating peritonitis (SEP) or encapsulating peritoneal sclerosis (EPS), is a rare cause of intestinal obstruction in which the small bowel is encased within a fibrocollagenous membrane, producing the prototypical frozen abdomen. Its surgical outcomes had never been pooled quantitatively. Objective: To quantitatively pool the surgical outcomes of adult abdominal cocoon — peri-operative mortality, morbidity, recurrence and pre-operative diagnostic yield — in patients undergoing operative management. Methods: PubMed, Scopus, the Cochrane Library and Google Scholar were searched for observational studies reporting the operative management and outcomes of adult abdominal cocoon. Ten case series (179 operated patients) were included. As all studies were single-arm, proportions were pooled with the Freeman–Tukey transformation under a DerSimonian–Laird random-effects model; robustness was tested with a logit-normal model, leave-one-out analysis and the Egger test, and quality with the Joanna Briggs Institute checklist. Results: Pooled peri-operative mortality was 4.5% (95% CI 0.2–12.1%; k=7); because zero-event studies influence the double-arcsine transformation, a logit-normal model gave 13.1% and the crude proportion 7.9%, so mortality is best summarised as low-to-moderate. Pooled morbidity was 19.5% (95% CI 5.9–36.9%; k=5), recurrence 3.3% (95% CI 0.0–21.8%; k=3) and pre-operative diagnostic yield 19.1% (95% CI 6.0–36.0%; k=4). Leave-one-out kept mortality between 3.0% and 8.5%. Conclusion: Surgery for adult abdominal cocoon achieved low-to-moderate mortality and acceptable morbidity with infrequent recurrence, supporting membrane excision and adhesiolysis in selected patients, while the low pre-operative diagnostic rate signals a need for greater awareness.